2011
DOI: 10.1093/bja/aer243
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to successful incident reporting in anaesthesia

Abstract: Editor-We note with interest in the report of NAP4 1 that serious airway difficulties were encountered more frequently with male patients, but are left wondering about the extent to which beards contributed to this sex difference. NAP4 undoubtedly helps us to shave risks: should it encourage us to shave chins?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Nurses could be trained to use personal digital assistants or smart phone applications to record their own time use patterns. This may result in more valid data on the time use of nurses [ 50 ] but at the loss of reflections-in-action, which the field researchers then used to refine the focus of their interview schedule. Alternatively, the field researchers could continue to record the data using tablet computers.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses could be trained to use personal digital assistants or smart phone applications to record their own time use patterns. This may result in more valid data on the time use of nurses [ 50 ] but at the loss of reflections-in-action, which the field researchers then used to refine the focus of their interview schedule. Alternatively, the field researchers could continue to record the data using tablet computers.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of an incident reporting scheme could in itself help to change the culture for the better as, if it is run properly with appropriate engagement and support from senior hospital management, it demonstrates that the 'no blame' approach is real and not an impossible fantasy. Some have suggested that couching the requirement to report incidents in terms of a professional ethical responsibility is effective 32 and indeed, a continual striving for improvement is one of the hallmarks of excellence in anaesthesia. 33 -35 The right culture can also be promoted through practical measures, such as the de-identification of reporters, protecting reporters and 'whistle-blowers' from unwarranted reprisals, and providing meaningful feedback.…”
Section: Discussionmentioning
confidence: 99%